Cell-Laden Agarose-Collagen Composite Hydrogels for Mechanotransduction Studies - Cambria, Elena; Brunner, Silvio; Heusser, Sally; Fisch, Philipp; Hitzl, Wolfgang; Ferguson, Stephen J.; Wuertz-Kozak, Karin (Frontiers in Bioengineering and Biotechnology, 2020)
The increasing investigation of cellular mechanotransduction mechanisms requires biomaterials combining biofunctionality and suitable mechanical properties. Agarose is a standard biomaterial for cartilage and intervertebral disc mechanobiology studies, but lacks adhesion motifs and the necessary cell-matrix interaction for mechanotransduction. Here, collagen type I was blended at two concentrations (2 and 4.5 mg/mL) with agarose 2% wt/vol. The composite hydrogels were characterized in terms of structural homogeneity, rheological properties and size stability. Nucleus pulposus (NP) cell viability, proliferation, morphology, gene expression, GAG production, adhesion and mechanotransduction ability were further tested. Blended hydrogels presented a homogenous network of the two polymers. While the addition of 4.5 mg/mL collagen significantly decreased the storage modulus and increased the loss modulus of the gels, blended gels containing 2 mg/mL collagen displayed similar mechanical properties to agarose. Hydrogel size was conserved over 21 days for all agarose-based gels. Embedded cells were viable (> 80%) and presented reduced proliferation and a round morphology typical of NP cells in vivo. Gene expression of collagen type I-II and aggrecan significantly increased in blended hydrogels from day 1 to 7, further resulting in a significantly superior GAG/DNA ratio compared to agarose gels at day 7. Agarose-collagen hydrogels not only promoted cell adhesion, contrary to agarose gels, but also showed a 5.36-fold higher focal adhesion kinase phosphorylation (pFAK/β-tubulin) when not compressed, and increased pFAK/FAK values 10 min after compression. Agarose-collagen thus outperforms agarose, mimics native tissues constituted of non-fibrillar matrix and collagens, and allows exploring complex loading in a highly reproducible system.